Molecular Structure Tailoring of Organic Spacers for High-Performance Ruddlesden–Popper Perovskite Solar Cells - Pengyun Liu; Xuejin Li; Tonghui Cai; Wei Xing; Naitao Yang; Hamidreza Arandiyan; Zongping Shao; Shaobin Wang; Shaomin Liu (Nano-Micro Letters)
Highlights Organic spacers in Ruddlesden–Popper (RP) perovskites play a vital role in tuning crystallization, charge transport and photovoltaic performance for RP perovskite solar cells (PSCs). Fundamental understanding of the functions of molecular structure of organic spacers is the prerequisite to design high-performance PSCs. This review proposes practical design strategies in seeking RP molecular structure to maximize its photovoltaic performance for PSCs.